Protective role of PERK-eIF2α-ATF4 pathway in chronic renal failure induced injury of rat hippocampal neurons. (1st February 2023) - Chen, Qi; Min, Jingjing; Zhu, Ming; Shi, Zhanqin; Chen, Pingping; Ren, Lingyan; Wang, Xiaoyi
Abstract: Purpose: Chronic renal failure (CRF) is associated with impairment of hippocampal neurons. This study investigated the effect of PERK-eIF2α-ATF4 pathway in CRF. Methods: Rat CRF model was established and rat hippocampal neurons were separated. Xanthine Oxidase method, fluorescence spectrophotometry and flow cytometry were applied to detect superoxide dismutase (SOD) content, reactive oxygen species (ROS) level and apoptosis in hippocampal neurons, respectively. The levels of phosphorylated (p)-PERK, phosphorylated (p)-eIF2α, CHOP, Bax, C-Caspase-3 and Bcl-2 in rats were measured using Western blot. Then, the neurotoxicity of serum from CRF rats was assessed in rat hippocampal neurons after treatment with rat CRF serum and transfection with or without PERK overexpression or knockdown plasmid. Results: SOD activity was reduced, while ROS level and apoptosis rate were increased in hippocampal tissues of CRF rats. PERK-eIF2α-ATF4 and apoptosis pathways were activated in CRF rats. Cells treated with serum from CRF rats showed increases in apoptosis rate and LDH and ROS levels, and decreases in cell viability and SOD activity. However, overexpressed PERK could reverse the cytotoxic effect of serum from CRF rats. PERK overexpression could enhance the activation of PERK-eIF2α-ATF4 pathway in hippocampal neurons induced by serum from CRF rats. Furthermore, PERK overexpression could alleviate the increases in CHOP, Bax, C-Caspase-3 expressions and the reduction of Bcl-2 expression in hippocampal neurons induced by serum from CRF rats. Conclusion: PERK-eIF2α-ATF4 pathway induced by increased endoplasmic reticulum stress may alleviate CRF-induced hippocampal neuronal damage.